GLOF event in the Turbio river basin in June 2017 (North Patagonian Andean Range, NW Chubut, Argentina): triggers and impacts - Quesada, Agustín (2022)
The Turbio river valley can be described as a paraglacial landscape with wide floodplainsand glaciers relicts in its headwaters. High-energy events, frequent but not cyclic, haveeffects on the geomorphological and biological evolution of the basin. Our study focuseson a glacial lake outburst flood (GLOF) that occurred in June 2017 in one of the upperbasin tributaries. Based on satellite images and local stakeholder’s information, the outburstoccurred between June 25th-26th. During those days, a rockslide from the southern slopeof the valley reached the lake (42,28°S; 72,13ºW), emptying it completely. The resultinghigh-energy flow eroded the lateral banks of the Turbio river valley and left a large debriscorridor extending more than 7 km. The torrent flood overbanks the lower fluvial plain andreached the fan delta of Puelo lake. Wood debris accumulations (Fitzroya cupressoides)were found along the Lake. A rural house was destroyed and trouts (Onchorynchus mykiss)were found dead. A few days before the event, a 3-day cumulative rainfall >80 mm wasdetected, associated with a cut-off low structure developed over the southeastern Pacific.Subsequently, on June 25th, a Mw 4.9 earthquake occurred 12 km from the lake, with adepth <13 km. In this case, the rockslide induced by weather (rainfall) or seismic conditions,or both combined, may have been sufficient to trigger a GLOF. An example is the Valdiviamega-earthquake of May 1960, in which outburst flood and avulsion processes werereported in the same lower basin. We suggest that continuous monitoring of glacial lakesand related hazards in this region is important, despite being sparsely populated. In addition,we recognize that the low anthropization degree of the Turbio river provides an excellentopportunity to study GLOFs and their geomorphic effects in the north Patagonian Andes.